Book Review: Martha C. Nussbaum, Not For Profit: Why Democracy Needs the Humanities. (January 2016) - Das, Amiya Kumar
Martha C. Nussbaum, Not For Profit: Why Democracy Needs the Humanities, 2012, Princeton and Oxford, MA: Princeton University Press, pp. 184, 15, ISBN: 978-0-691-15448-0 (Paperback).